Vaccination in Nile tilapia broodstock with whole cell vaccine and disease resistance in its fry against Aeromonas hydrophila - Sukenda, Sukenda; Carman, Odang; Rahman, Rahman; Hidayatullah, Dendi; Yumaidawati, Nurfitriani Siti (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACT The aim of this study was to analyze the effectivity of vaccination in Nile tilapia broodstock with whole cell vaccine and disease resistance in fry tilapia against Aeromonas hydrophila. Tilapia Nirwana strain that used for this had average body weight of 185±13.23 g and were maintained in ponds sizing of (2.5×2.5×1 m3). Vaccinations that has been done through intraperitoneal injection using dose of 0.1 mL/fish, meanwhile the fish for control was injected by phosphate buffered saline (PBS). This study used complete randomized design with two treatments and three replications. Antibody level was measured by using indirect enzyme-linked immunosorbent assay (ELISA) method in the broodstock, egg, and fry. Challenge test in fry tilapia performed at the age of 5, 10, and 15 days. The results showed that vaccination in tilapia broodstock delivered a significant antibody level in broodstock, eggs, and fry (P<0.05) compared to the control. Relative percent survival of offspring at 5, 10, and 15 days were 78.26%, 70.59%, and 65.52%, respectively. As a conclusion, vaccination in tilapia broodstock was effective to improve specific and non-specific immunity, and protect fry tilapia from A. hydrophila infection through maternal immunity. Keywords: vaccination, antibody, maternal immunity, tilapia, Aeromonas hydrophila ABSTRAK Penelitian ini bertujuan untuk menganalisis efikasi vaksinasi pada induk nila dengan vaksin sel utuh dan ketahanan benih yang dihasilkan terhadap Aeromonas hydrophila. Ikan nila stain Nirwana yang digunakan dalam penelitian memiliki bobot rata-rata 185±13,23 g dan ikan dipelihara dalam kolam (2,5×2,5×1 m3). vaksinasi dilakukan melalui penyuntikan intraperitoneal dengan dosis 0,1 mL/ikan, sementara itu ikan kontrol disuntik dengan phosphate buffered saline (PBS). Penelitian ini menggunakan rancangan acak lengkap dengan dua perlakuan dan tiga ulangan. Tingkat antibodi diukur dengan menggunakan metode indirect enzyme-linked immunosorbent assay (ELISA) pada induk, telur dan benih. Uji tantang pada benih dilakukan pada umur 5, 10, dan 15 hari. Hasil penelitian menunjukan bahwa vaksinasi pada induk nila secara signifikan dapat meningkatkan level antibodi pada induk, telur, dan benih (P<0,05) dibandingkan dengan kontrol. Kelangsungan hidup relatif pada benih berumur 5, 10, dan 15 hari masing-masing adalah 78,26%; 70,59%; dan 65,52%. Sebagai kesimpulan vaksinasi pada induk nila efektif dalam memperbaiki imunitas spesifik dan non spesifik serta melindungi benih dari infeksi A. hydrophila melalui imunitas maternal. Kata kunci: vaksinasi, antibodi, imunitas maternal, ikan nila, Aeromonas hydrophila